196k views
5 votes
Solve for X:
1/3x+2/3=1/4x-1/6

Step by step please

1 Answer

5 votes

Answer:

For the given expression
((1)/(3))x +  ((2)/(3))  =   ((1)/(4))x  - ((1)/(6)) , x = -10

Explanation:

Here, the given expression is :
((1)/(3))x +  ((2)/(3))  =   ((1)/(4))x  - ((1)/(6))

Now, solving for x:

Separate the terms with x on one side, we get


((1)/(3))x      -   ((1)/(4))x  =   - ((1)/(6))  -   ((2)/(3))

or,
((1)/(3)      -   (1)/(4))x  =   - ((1)/(6)  +   (2)/(3))\\\implies ((4-3)/((3)(4))) x = -((1+ 2(2))/(6) )

or,
(1)/(12)x  = - (5)/(6) \\\impliex x  = -(5)/(6)  * 12   = -10

or, x = -10

Hence, for the given expression
((1)/(3))x +  ((2)/(3))  =   ((1)/(4))x  - ((1)/(6)) , x = -10

User Ankit Jaiswal
by
5.0k points